Constructing a living theory of change in fluid and volatile environme nts: Grounded on context, problem, and evidence - Hassnain, Hur (Theories of Change in Reality, 2024)
Theory of change is an explicit articulation of how an intervention cr eates an intended result to address a specific problem. This ‘theory’ is difficult to re/construct if the ‘context’ is complex, conflict-rid den, and uncertain. In such contexts, causal linkages leading to a des ired outcome tend to be messy, multilevel, multidirectional, and unpre dictable, as plans and strategies often do not work as anticipated. Wh ilst some activities lead to outcomes, others do not. Outcomes (positi ve or negative) could also emerge in unexpected places. This essay dis cusses why and how evaluations in fluid and volatile environments must aim to tackle the emergence and unpredictability of outcomes, and re/ construct a theory together with key stakeholders. This ensures that i t is fully grounded in the context, problem, and available evidence at the inception stage of the evaluation process and onwards. Preferably , evaluators should be engaged from the design of the intervention and its theory of change because a lack of understanding of the context r esults in causing harm to individuals, groups, and organisations and c reates a lack of realism about the capacity of external actors to supp ort substantive positive change. A better understanding of the context can help illustrate the causal links, hypotheses, and assumptions tha t make evaluations reliable and safe for the enumerators, evaluators, and the affected population. It also aids in assessing whether the int ervention has had a positive or negative effect or no effect at all.